(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the mean duration of labour after injection of Drotaverine hydrochloride in primigravida presenting in active phase of labour in a tertiary care hospital. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Department of gynecology and obstetrics Bacha khan medical complex Sawabi from January to July 2018. Materials and Methods: A total of 123 patients were enrolled in the study after taking informed consent from the individual participant. Patients having age 20-36 years with singleton cephalic presentation of fetus as assessed on ultrasound and already in the active phase of labour having cervical dilation of 3-5cm with 2-3min uterine contractions for at least 30 seconds in every 10 minutes were included in the study. Data was collected using a pre designed proforma. Data analysis was done using SPSS version 20. Results: Average age of the patients was 25.72years+3.67SD with range 20-36 years. Average gestational age of the patients was 37.26 years+2.29SD with range 33-41 weeks. The average total duration of average labor was 4.14±0.55SD. Conclusion: Drotaverine hydrochloride in primigravida presenting in active phase of labour is effective to reduce the duration of labor